FORMULASI NANOEMULGEL EKSTRAK KULIT MANGGIS (Garcinia Mangostana L.) - Damayanti, Hilda; Wikarsa, Saleh; Jafar, Garnadi (Jurnal Riset Kefarmasian Indonesia, 2019)
Antioxidant-containing cosmetic has antiaging therapy that can inhibit the free radical formation. Mangosteen peel extract has very strong antioxidant activity. To enhance the effect and comfortness of mangosteen peel extract use on the skin, it could be made into nanoemulgel. The article provides the information about method of preparation and evaluation of nanoemulsion-gel. The purpose of this study was to formulate a stable microemulgel of mangosteen peel extractusing halal materials declared halal according to Islamic Shari’a. the materials used don’t contain carrion, blood, pig and/ animals that don’t conform to Islamic Shari’a. Microemulgel mangosteen peel extract was made by varying plantacare® 1200 UP concentration as cosurfactant (5, 10, 15, 20 and 25%) in the microemulsion and it was incorporated into the gel base. Evaluations were included the antioxidant activity test and organoleptic, pH, viscosity, stability, particle size analysis and panelist test. The antioxidant activity determined by DPPH method showed that IC50 value of mangosteen peel extract was 5.54 ppm. The third microemulsion formula containing cosurfactant of 15% resulted in the best results in that the parameter of the product can be penetrated by ray laser was at particle size of 23.65 nm, was determined by tranmission Electron Microscopy (TEM). Microemulgel containing Viscolam® MAC 10 of seven percent gave the stable formula proofed by freeze thaw and sentrifuga test. The five microemulgel formulations were stable.